2011
DOI: 10.1369/0022155411423680
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Cancer Histoid

Abstract: SummaryProgress in our understanding of heterotypic cellular interaction in the tumor microenvironment, which is recognized to play major roles in cancer progression, has been hampered due to unavailability of an appropriate in vitro co-culture model. The aim of this study was to generate an in vitro 3-dimensional human breast cancer model, which consists of cancer cells and fibroblasts. Breast cancer cells (UACC-893) and fibroblasts at various densities were co-cultured in a rotating suspension culture system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Therefore, these tumor constructs can be used to model bulky tumors with regions of low proliferative activity and increased drug resistance (Becker and Souza, 2013). Various tumor models, including hepatocellular carcinoma (Chang and Hughes-Fulford, 2009), neuroblastoma (Redden and Doolin, 2011), breast adenocarcinoma (Kaur et al, 2011), and melanoma (Marrero et al, 2009), have been successfully engineered using RWV-based bioreactors. This type of bioreactor also has been utilized for the ex vivo culture of tissue explants.…”
Section: Device-assisted Assembly Of Tumor Modelsmentioning
confidence: 99%
“…Therefore, these tumor constructs can be used to model bulky tumors with regions of low proliferative activity and increased drug resistance (Becker and Souza, 2013). Various tumor models, including hepatocellular carcinoma (Chang and Hughes-Fulford, 2009), neuroblastoma (Redden and Doolin, 2011), breast adenocarcinoma (Kaur et al, 2011), and melanoma (Marrero et al, 2009), have been successfully engineered using RWV-based bioreactors. This type of bioreactor also has been utilized for the ex vivo culture of tissue explants.…”
Section: Device-assisted Assembly Of Tumor Modelsmentioning
confidence: 99%
“…Mixed spheroids have been used to study tumor-stromal cell interactions and the cells in these mixed spheroids have a more in vivo cell shape, architecture, and gene expression profiles 79, 80 . For example, breast cancer cells co-cultured with fibroblasts showed an invasive phenotype and formed a tissue more similar to primary breast cancer tissue in terms of protein expression in the cancer cells (pancytokeratins, p53, E-cadherin) and the fibroblasts (vimentin) compared 81 . Three dimensional tumor-endothelial cell models have been used to measure the angiogenic and metastatic potential of tumor cells and the presence of endothelial cells makes tumor cells more resistant to chemotherapy and radiation 82, 83 .…”
Section: Applications Of Spheroids and Microtissuesmentioning
confidence: 99%
“…Several studies have reported on the co-culture of breast cancer cells with fibroblasts [74,8286], with immune cells such as macrophages [87,88] or with adipocytes [8992] generally using lrECM, collagen or spheroid models and demonstrated their reciprocal communication and the effect of stromal cells on the behavior and signaling of breast cancer cells (see below). It should be noted, however that the effect of stromal cell lines on gene expression or drug response has also been examined using transwell assays or direct co-culture of stromal and breast cell lines in conventional 2D monolayers [9395].…”
Section: Heterotypic Three-dimensional Cell Culture Modelsmentioning
confidence: 99%